E‐Health self‐management intervention for oral and oropharyngeal cancer survivors: design and single‐arm pilot study of empowered survivor. Issue 11 (23rd August 2020) - Manne, Sharon; Hudson, Shawna; Frederick, Sara; Mitarotondo, Anna; Baredes, Soly; Kalyoussef, Evelyne; Ohman‐Strickland, Pamela; Kashy, Deborah A.
Abstract: Background: Self‐management regimens for oral and oropharyngeal cancer survivors can be complex and challenging. Effective self‐management skills can foster better outcomes. We report on the development, feasibility, and pilot testing of a web‐based self‐management tool called "Empowered Survivor" (ES) for survivors of oral and oropharyngeal cancer. Methods: ES content was developed in two phases, with modules focusing on oral care, swallowing and muscle strength, and long‐term follow‐up. This single‐arm pilot study consisted of a pre‐, 2‐month, and a 6‐month postintervention survey. Results: Enrollment rates were relatively low. Once enrolled, data collected from the ES website indicated that 81.8% viewed ES. Participants provided positive evaluations of ES. Preliminary results indicate that ES had a beneficial impact on self‐management self‐efficacy, preparedness for survivorship care, and quality of life. ES improved survivors' engagement in oral self‐exams and head and neck strengthening exercises, improved ability to address barriers, and decreased information and support needs. Conclusions: This study provides preliminary evidence of engagement, acceptability, and beneficial impact of ES, which should be evaluated in a larger controlled clinical trial.